Espaço público e socialidades impressas: o estilo cotidiano nas colunas sociais - Galdino, Tarcineide Mesquita (2013)
The dissertation verify how the social columns in newspapers of João Pessoa and his particular way of building everyday, watching narratives about public space, socialities existing forms and lifestyles. It starts with the conjecture that social columns in the daily press displays diverse aspects of everyday life. These aspects are legitimated by the tematic fragmentation of jornalism that tends, among other things, to bring the audience to thier products. Because of the peculiarities that have the gossip columns, cutting theme fits in this genre, a range of subjects ranging from the frivolus and playful aspects of daily life to more serious aspects witn a focus on public interest, such as politics. It analyses the columns Abelardo Jurema (Journal Correio da Paraíba), Geraddo (Jornal da Paraíba) and Goretti Zenaide (Jornal o Norte), hsving as theoretical-methodological theories of journalistic genres; Sociology of evereyday life and the key concepts that emerging theory of Michael Maffesoli. The formismo, tissue from the notion "from" was used as a method of procedure. The analysis shows that the empirical object on the daily gossip columns can be read from identify how the imaginary and the identifications of groups such as the elite, are present in everyday life, transforming it into a field appropriate to question the aesthetic experiences and lifestylees of contemporary subjects.